A Survey on forensic odontologists' activity in Italy during the COVID-19 pandemic. (April 2023) - Bianchi, Ilenia; Pradella, Francesco; Vitale, Giulia; De Luca, Stefano; Castello, Fiorella Pia; Focardi, Martina; Pinchi, Vilma
Abstract: Few information on virus contagion at the beginning of the covid-19 pandemic led to severe restrictions in the dental and forensic activity in Italy, the introduction of procedural guidelines and implementation of preventive measures. A specific survey on Italian forensic odontologists (FOds) activity was conducted to investigate the COVD-19 pandemic impact on daily practices, the preventive measures adopted to manage the risks of contagion procedures performed on living and dead people and the possible peculiar cases that required the intervention of a medical examiner. A total of 122 FOds answered, mostly males over 46 years coming from northern Italy. The results highlight the lack of specific guidelines for the procedures on living people compared to those on the dead but the regulations for the daily clinical practice resulted more than sufficient: in fact, more than 80% of FOds adopted the preventive and safety measures provided for dental practices. The forensic activity significantly decreased during the initial period (more than 75%) and gradually normalized to pre-pandemic numbers in approximately 50% of cases after the implementation of the vaccination campaign. 13 cases of occupational contagion have been reported, most of them (more than 85%) in northern and central Italy. In two cases members of the dental staff sued the employer for responsibility in the contagion. The decrease of the overall ID activity during the pandemic time can be more likely attributed to the of the dental data than the real impact of the pandemic regulations. The use of telematic tools, such as teleconferences, for many procedures proved to be an important resource useful for application even in post-pandemic times. Highlights: The COVID-19 pandemic strongly disrupted any health and forensic activity. A survey investigated the COVID-19 impact on Italian forensic odontologists' activity. A decrease in assignments and an increase in safety measures were highlighted. Cases of occupational contagion and employer's responsibility were reported. The low reported identification activity during the pandemic seems to be related to the underuse of dental data.